Assessment of Visual, Auditory and Kinesthetic Style of Learning among Undergraduate Nursing Students of Sindh: Vak Style of Learning - Soomro, Lubna; Ali, Muhammad; Sohu, Firdous; Mustafa, Mir Ghulam; Ansari, Muhammad Ibrahim (Pakistan Journal of Health Sciences, 2023)
Learning styles refer to the ability of learner to perceive and process information in learning framework. Visual, Auditory, and Kinesthetic are modes by which students use three sensory perceptions to receive information. Objective: To assess visual, auditory, and kinesthetic learning style among nursing students. Methods: Cross sectional study among students of diploma in general nursing, of nursing schools of Jacobabad and Jamshoro- conducted during May- October 2017 with sample size of 88 via simple random sampling. After the approval, the data were collected from the concerned school with their permission. Data were entered into SPSS 23.0 version in which frequency, percentages were generated and chi square were applied. Results: Eighty-eight participated in among them 52(59.1%) were from SON-LUH (Female) Jamshoro and 36(40.9%) were from SON (Male) Jacobabad. Most of the students were from 2nd and 3rd year 34(38.6%) and 36(40.9%). Auditory style of learning was at the highest among male students 36.12% whereas females were at the highest in visual style of learning 34.62%. Forty years students learnt at the highest in visual and kinesthetic style of learning 3311%. Conclusions: Undergraduate nursing students of both gender & academic years were equally inclined towards all learning styles.